1992
DOI: 10.1139/f92-240
|View full text |Cite
|
Sign up to set email alerts
|

Bias in Hydroacoustic Estimates of Fish Abundance due to Acoustic Shadowing: Evidence from Day–Night Surveys of Vertically Migrating Fish

Abstract: We investigated the hypothesis that fish schooling behavior leads to underestimation of fish abundance when assessed by acoustic methods. Current methods for acoustic quantification of fish abundance rely on the assumption that fish biomass and numerical fish abundance are linearly related to acoustic scattering under all natural fish densities. However, cage experiments as well as field observations have indicated that acoustic shadowing effects occur at very dense and large aggregations of fish. Acoustic sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
2
1

Year Published

1995
1995
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 1 publication
2
43
2
1
Order By: Relevance
“…Such measurements have been described by many other authors, for example, , MacLennan and Simmonds (1992), Guillard (1991), and Appenzeller and Legget (1992).…”
Section: Methodsmentioning
confidence: 57%
“…Such measurements have been described by many other authors, for example, , MacLennan and Simmonds (1992), Guillard (1991), and Appenzeller and Legget (1992).…”
Section: Methodsmentioning
confidence: 57%
“…Schooling behavior can influence the efficiency of trawling and acoustic methods of population assessment . Appenzeller & Leggett (1992) found that acoustic shadowing resulted in a 50% underestimate of rainbow smelt, Osmerus mordax, abundance during daytime sampling, when smelt were aggregated in dense schools, compared to nighttime sampling, when smelt were dispersed .…”
Section: Introductionmentioning
confidence: 94%
“…Although other senses, such as the lateral line system, may play an important role in the spatial and angular orientation of individuals within a school (Partridge & Pitcher 19801, it is unlikely that in the wild many species are capable of schooling in the absence of sufficient light. Thls impression is supported by observational (Emery 1973, Helfman 1979 and bioacoustical studies which generally show that shoals and schools disperse at night (Appenzeller & Leggett 1992, Brodeur & Wilson 1996. Since ambient light in marine and aquatic habitats may vary greatly according to depth, turbidity, season, lunar stage and cloud cover (McFarland 1986), the meaning of 'night', relative to light levels, 1s rather ambiguous.…”
Section: Introductionmentioning
confidence: 95%